An audit on diabetic patient understanding on technique of insulin injection in Hospital Raja Perempuan Zainab II / Nik Farahana Ruslan, Roslan Mohammad and Mohd Supardi Mohd Fozi - Ruslan, Nik Farahana; Mohammad, Roslan; Mohd Fozi, Mohd Supardi (2010)
The purpose of this project is to describe patient understanding in technique of pen fill insulin use and the role of insulin. In this study seems to be important as to know how deep knowledge of diabetic patient, factors influences, and parts should be focused for improvement. It has been run in Pharmacy Outpatient Department of Hospital Raja Perempuan Zainab (11) for 2 months. We use patient questionnaire to collect data. If Before staff nurse also take part in patient counselling now only pharmacist will take care about patient counselling before use or do insulin injection. Contain of the counselling should be focused to increase patient knowledge. Inadequate information and inappropriate technique in educating patient can lead to wrong patient practise. Only education level and counselling standing is appeared to be important in affecting patient knowledge compare to others demographic detail and patients’ history such as age, race, education level, year of experience in taking penfill insulin, counselling standing from the survey we can indicated that, patient not really understand about diabetes, insulin and the right and complete technique to use penfill insulin. Many of the patients are elderly and need proper counselling from trained personnel who pursue official guideline provided